1989
DOI: 10.2519/jospt.1989.10.8.297
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Torque Generating Capabilities of Three Different Electrical Stimulating Currents

Abstract: The purpose of this study was to test the torque generating capabilities of three commercially available neuromuscular electrical stimulators (NMES) having different current characteristics.Twenty healthy adults were positioned in sitting on an isokinetic dynamometer. Maximum voluntary isometric knee extension torque was determined. Subsequently, two 10-sec, maximally tolerated contractions were elicited with each machine. The order of stimulation was randomized and there were 2-minute rest periods between con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
33
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 11 publications
6
33
1
Order By: Relevance
“…The 2 stimulators that generated the same phase charge per waveform, either a 200-microsecond (phase duration) sine wave or a 200-microsecond (phase duration) symmetrical biphasic rectangular wave, produced the same electrically induced maximum quadriceps torque (%MVIC) (P Ͼ.05); but both stimulators produced significantly greater %MVICs (PϽ.05) than a stimulator that generated a 125-microsecond (phase duration) sine wave. 13 Similarly, in our study, the waveforms with the most charge produced the greatest quadriceps muscle force at equivalent current intensities.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The 2 stimulators that generated the same phase charge per waveform, either a 200-microsecond (phase duration) sine wave or a 200-microsecond (phase duration) symmetrical biphasic rectangular wave, produced the same electrically induced maximum quadriceps torque (%MVIC) (P Ͼ.05); but both stimulators produced significantly greater %MVICs (PϽ.05) than a stimulator that generated a 125-microsecond (phase duration) sine wave. 13 Similarly, in our study, the waveforms with the most charge produced the greatest quadriceps muscle force at equivalent current intensities.…”
Section: Discussionmentioning
confidence: 60%
“…In support of this interpretation, Ward and Shkuratova 15 reported that the current amplitudes required to produce 60% of the maximum wrist and finger flexor EIT decreased at lower carrier frequencies. In addition, Snyder-Mackler et al 13 compared the quadriceps torque generating ability of 3 different electrical stimulators. Each stimulator produced a different waveform.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The trunk was also stabilized with belts in order to avoid possible muscular compensations. The dynamometer was programed at angle velocity of 0° per second (isometric mode), and the knee joint of the dominant leg was positioned at 60º of flexion, and the dynamometer's arm rest was placed on the distal region of the volunteer's leg, which allowed a complete dorsiflexion arch 12,[21][22][23] . During the tests 1 and 2, the volunteers were verbally encouraged by the examiner to perform the highest strength as possible.…”
Section: Methodsmentioning
confidence: 99%